PENDAMPINGAN BANGUNAN TAHAN GEMPA DI DESA BATURSARI KECAMATAN SAPURAN KABUPATEN WONOSOBO - Poerwodihardjo, F. Eddy; Rachmanudin, M. Edwin; Selalatu, Dadi Tri Awan (Universitas Wijayakusuma Purwokerto, 2025)
A sense of security is a basic human need in living life at home. This sense of security can be realized through building structures and construction that are able to withstand frequent earthquakes. Even though earthquake-resistant building technology has long been available, many people do not understand it, including in Batursari Village, Sapuran District, Wonosobo Regency. Therefore, knowledge transfer and assistance is needed to help communities create homes that are safe and able to withstand earthquakes. The community service team voluntarily helps the community in building earthquake-resistant houses using systematic steps. The activity began with education about earthquake-resistant buildings to provide basic understanding to the community. Next, the team provided assistance to one of the residents who was planning to build a house. This process includes surveying and measuring the location, creating plan drawings in the form of plans, views and other complementary drawings. After the homeowner approves the plans, construction costs are estimated. The final stage of this assistance activity is the preparation of a report on the construction of an earthquake-resistant house. Although building an earthquake-resistant house requires additional costs, the amount is not too significant. By implementing the right techniques, the benefits of an earthquake-resistant house are much greater and commensurate with the investment spent. A house that is safe from earthquakes not only provides a sense of calm but also protects residents from the risk of disaster.